Beta relaxation theory for simple systems : some addenda - Fuchs, Matthias; Götze, Wolfgang; Hildebrand, S.; Latz, Arnulf (My University, 1992)
The evolution of the tagged particle probability density for a hard sphere system is evaluated within the B-relaxation window. Relaxation curves obtained by molecular dynamics studies by Barrat, Hansen and Roux for a binary mixture are analyzed quantitatively with B-relaxation scaling formulae. The dynamical light scattering data obtained by Pusey and van Megen for colloidal suspensions are described by the combined a- and B-relaxation scaling results. The range of validity of asymptotic expressions near a glass transition singularity is discussed for the Debye-Waller factor as a function of packing fraction. The applied theoretical formulae are those of the mode coupling theory for the liquid to glass transition.
Keywords: 530